Virtual to Reality Emulator for Electrical Loads - Luis, Gomes (2021)
The test and validation of demand side management systems are a priority before installing this systems in real environments. This paper presents a load emulator that acts as an energy analyzer. This emulator enables its installation in physical environments, fooling the metering systems. This capability allows the placement of the emulator in a physical metering system while emulating a load that is not there. In a R&D center the emulator can be used to create buildings by placing several emulators for load emulation and using a real and physical metering system to read the consumption data while demand side management algorithms and techniques are used. Using the proposed emulator, the gap between research and real implementations can be fulfill in the laboratories to test and validate demand side management systems. The paper presents the emulator and its results.